2003
DOI: 10.1259/dmfr/15999089
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of digital and film panoramic radiographs for assessment of position and morphology of mandibular third molars and prevalence of dental anomalies and pathologies

Abstract: The five digital panoramic systems evaluated in this study were equally as useful for third molar treatment planning and diagnosis of dental anomalies and pathologies as conventional film-based panoramic radiographs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
6

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 17 publications
0
13
0
6
Order By: Relevance
“…5 Panoramic radiography is usually the first radiographic method used to evaluate the location of the MC. [6][7][8][9] However, the information it provides is only two-dimensional and the images are distorted, often resulting in miscalculation of the location of the MC. planning, 4,10,11 and both have recently been replacing conventional panoramic radiographs.…”
Section: Introductionmentioning
confidence: 99%
“…5 Panoramic radiography is usually the first radiographic method used to evaluate the location of the MC. [6][7][8][9] However, the information it provides is only two-dimensional and the images are distorted, often resulting in miscalculation of the location of the MC. planning, 4,10,11 and both have recently been replacing conventional panoramic radiographs.…”
Section: Introductionmentioning
confidence: 99%
“…In the digital system, the film-based image is replaced by a two-dimensional array of pixels. There are several studies investigating on the accuracy and precision of digital panoramic radiographs and most of the reports concluded that the digital panoramic system was equally as useful as conventional film-based panoramic radiographs (4,5). However, it was also reported that panoramic radiography had limitations of distortion, superimposition with variability in inter-examiner agreement (6).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have compared solid state sensors (2 systems, 52 and 93 teeth) and PSP systems (3 systems, 62, 104 and 77 teeth) with film for panorama imaging assessing third molars before removal and found that accuracy differed little for most of the variables evaluated, although two of the three PSP systems had significantly lower accuracy than film for assessing the relationship to the canal. 4 Those PSP systems were not included in the present study.…”
Section: Resultsmentioning
confidence: 99%
“…2 Digital receptors for panoramic imaging of the third molar have previously been evaluated (both chargecoupled device (CCD) sensors and photostimulable storage phosphor (PSP) plate systems) and it was concluded that five digital systems were equally useful for third molar treatment planning and had similar diagnostic accuracy. 3,4 One study, however, demonstrated that a CCD-based device was less accurate than PSP systems and film for diagnosing morphological changes in the temporomandibular joint (TMJ). 5 Previous studies using conventional film have evaluated scanograms for assessment of mandibular third molars and concluded that scanography was a useful method for evaluating the buccolingual relations between the mandibular canal and the roots of the molar.…”
Section: Introductionmentioning
confidence: 99%